2022
DOI: 10.5194/acp-22-2029-2022
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal distribution of size-resolved particle effective density: results from a short campaign in a rural environment over the North China Plain

Abstract: Abstract. Effective density is one of the most important physical properties of atmospheric particles. It is closely linked to particle chemical composition and morphology and could provide special information on particle emissions and aging processes. In this study, size-resolved particle effective density was measured with a combined differential mobility analyzer–centrifugal particle mass analyzer–condensation particle counter (DMA–CPMA–CPC) system in autumn 2019 as part of the Multiphase chemistry experime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…As mentioned in Section 2.4, the particle density is needed for the κ calculation; however, in this campaign, direct measurements of particle density were not available. As a reference, a value of 1.5 g cm −3 was used for particle density, considering the typical range of particle density values found in literature (Geller et al., 2006; Hu et al., 2012; Levy et al., 2013, 2014; Rissler et al., 2014; Zamora et al., 2019; Zhou et al., 2022). By assuming spherical particles and using a reference particle density value, the hygroscopicity parameter κ can be calculated from the measured D m at a specific SS using the κ ‐Köhler theory.…”
Section: Application Of the Aac‐ccnc System On The Tpmentioning
confidence: 99%
“…As mentioned in Section 2.4, the particle density is needed for the κ calculation; however, in this campaign, direct measurements of particle density were not available. As a reference, a value of 1.5 g cm −3 was used for particle density, considering the typical range of particle density values found in literature (Geller et al., 2006; Hu et al., 2012; Levy et al., 2013, 2014; Rissler et al., 2014; Zamora et al., 2019; Zhou et al., 2022). By assuming spherical particles and using a reference particle density value, the hygroscopicity parameter κ can be calculated from the measured D m at a specific SS using the κ ‐Köhler theory.…”
Section: Application Of the Aac‐ccnc System On The Tpmentioning
confidence: 99%
“…However, several studies have reported that particle density might vary between 1 and 2.5 g cm −3 . 67,69,72,74,[76][77][78] To account for the ambient particle density variation, we also include d p,50,theo calculated by using r p equal to 1 and 2.5 g cm −3 as uncertainties in Table 1.…”
Section: Laboratory Evaluation Of Collection Efficiency Of Each Impac...mentioning
confidence: 99%